2013
DOI: 10.1016/j.athoracsur.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Completion Pneumonectomy: Outcomes for Benign and Malignant Indications

Abstract: Background Past series have identified completion pneumonectomy (CP) as a high-risk operation. We evaluated factors affecting outcomes of CP with a selective approach to offering this operation. Methods We analyzed a prospective institutional database and abstracted information on patients undergoing pneumonectomy. Patients undergoing CP were compared to those undergoing primary pneumonectomy (PP). Results Between 1/2000 and 2/2011, 211 patients underwent pneumonectomy, of which 35 (17%) were CPs. Ten of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
0
13
1
1
Order By: Relevance
“…Whether preoperative chemotherapy or radiotherapy increases operative mortality also remains unclear, as studies have found conflicting results [ 18 , 19 ]. Completion pneumonectomy has also been reported as a predictive risk factor for postoperative death [ 10 ]; however, other authors were not able to confirm these findings [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether preoperative chemotherapy or radiotherapy increases operative mortality also remains unclear, as studies have found conflicting results [ 18 , 19 ]. Completion pneumonectomy has also been reported as a predictive risk factor for postoperative death [ 10 ]; however, other authors were not able to confirm these findings [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Median survival was significantly better in CP patients who had not received neoadjuvant therapy (34.6 months vs. 11.9 months, p= 0.003). Puri et al [33] reported this as 24 months for benign CP and 36 months for malignant CP. Parallel to our study, Tabutin et al [18] stated that survival was significantly better particularly in young patients.…”
Section: Discussionmentioning
confidence: 98%
“…To secure our patient’s airway, a 7.0-mm spiral tube was inserted via the nasal route, and tracheostomy was performed for insertion of the DLT before exploration of the lung. Several researchers have previously reported that completion pneumonectomy has a 20–23% perioperative mortality [7] , [8] , and patients undergoing completion pneumonectomy due to benign conditions had a higher comorbidity and mortality than those with malignancy [9] . Fortunately, pneumonectomy was avoided in our patient, but it is important to consider this strategy when the patient has life threatening hemodynamic and respiratory problems.…”
Section: Discussionmentioning
confidence: 99%